EU-wide income inequality in the era of the Great Recession - Peter Benczur; Zsombor Cseres-Gergely; Peter Harasztosi (Publications Office of the European Union, 2017)
This paper uses European micro-data to look at stylised facts of EU-wide income inequality during the 2006-2013 period. Our contribution is to bring together four elements of the analysis that has appeared only in separation so far. Our analysis is EU-wide, but regionally detailed, looks at the longest possible term with harmonized survey data, uses inequality indicators sensitive to different parts of the income distribution and shows the contribution of different income components to income inequality. To our knowledge, this is the first attempt to produce stylised facts with these features at the same time, which, we believe is important in order to ask and answer questions related to the welfare of the people of the EU as a whole. We also take great care of rendering our work as homogeneous and transparent as possible. Because of this, we believe that the evidence we provide can be a starting point to a line of research on EU-wide income inequality.
Keywords: D31; E24; H31; J31; 330; income inequality; European Union